Effects of salt stress on growth and physiological characteristics of Chamerion angustifolium seedlings - Zhang, Caiwei; Liu, Xiaojuan (Frontiers in Plant Science, 2025)
BackgroundSoil salinity is a major abiotic stressor that inhibits plant growth. Assessing the salt tolerance of Chamerion angustifolium (L.) Holub is crucial for understanding its potential in saline environments.MethodsIn this study, C. angustifolium seedlings were grown in pots in soil culture, and three concentration gradients of NaCl (50 mmol∙L-1, 100 mmol∙L-1, 150 mmol∙L-1) were set to correspond to mild, moderate and heavy salt stress, respectively; the stress time of 5 d, 10 d and 15 d were set to correspond to short, medium and long time stress. With soil water content of 90%±5% and salt concentration of 0 mmol∙L-1 as control, we carried out salt stress treatments to determine the changes of morphological and physiological indices in C. angustifolium seedlings under different salt stress levels and different stress times, and to explore the tolerance of C. angustifolium seedlings to salt stress.Results(1) NaCl stress significantly inhibited the morphological growth of C. angustifolium seedlings (P < 0.01). For instance, at 150 mmol·L-1 NaCl for 15 days, plant height and leaf area were reduced by approximately 89% and 79%, respectively, compared to the control. Concurrently, osmoregulatory substances such as proline increased markedly, reaching up to 34.7-fold of the control level under severe stress, while antioxidant enzyme activities (e.g., superoxide dismutase, peroxidase) also rose significantly, by up to 393% and 133%, respectively. In contrast, chlorophyll content and leaf relative water content decreased substantially, with total chlorophyll declining by over 50% under the highest salt concentration. With prolonged stress duration, the morphological indices of C. angustifolium exhibited a decreasing trend under mild, moderate and severe NaCl stress, a 79% decrease in leaf width under severe stress after 15 days. Meanwhile, the content of osmoregulatory substances and the activity of antioxidant enzymes increased continuously over time across all NaCl concentrations, while chlorophyll content and relative water content consistently declined. (2) Principal component analysis identified malondialdehyde, chlorophyll a, chlorophyll b, and proline as key indicators for screening and evaluating salt tolerance in C. angustifolium seedlings.ConclusionC. angustifolium can be classified as a species with moderate salt tolerance, capable of surviving short-term exposure to 100 mmol·L-1 NaCl but at the cost of substantially reduced growth.